RUPTURED ABDOMINAL AORTIC ANEURYSM POST-EVAR DUE TO COMBINED TYPE II AND IA ENDOLEAK – AN INVENTIVE SOLUTION TO A THERAPEUTIC CHALLENGE - Coelho, Andreia Pires (2018)
Introduction: Endovascular aortic repair (EVAR) has significantly altered the therapeutic strategy for abdominal aortic aneurysm (AAA), due to less invasiveness and lower perioperative morbi-mortality. However, specific complications such as type 1a endoleak (T1aE) and persistent type 2 endoleak (pT2E) have been associated with adverse outcomes including aneurismal rupture. We present a case of AAA rupture due to both T1aE and pT2E treated in our institution. Case Report: The patient is a 73-year-old male, submitted to EVAR at another institution for infra-renal AAA with no apparent complications. He was admitted in the emergency department, 7 years post-EVAR, with abdominal pain and loss of consciousness with spontaneous recovery. A CTA was performed and revealed aneurysmal sac growth, spontaneous hiperdensity of the thrombus, high density in the fat in the right retroperitoneum and a pT2E. Intra-operatively, after opening the aneurysmal sac, both pT2E and T1E were detected. He was submitted to partial aneurismectomy, suture of the ostia of the lumbar arteries, filling of the aneurysm sac with prothrombotic products and closure of the aneurysm sac with adjustment of the proximal sealing zone. The patient was discharged 15 days post-procedure. CTA performed 1 month after the procedure revealed no endoleak, aneurismal sac stability filled with prothrombotic products. At 2-year follow-up the patient remained asymptomatic and the CTA findings remained unchanged. Discussion: Rupture post-EVAR is a significant therapeutic challenge for vascular surgeons. In this case, pre-operative CTA findings lead to plan an open surgery with endoaneurismorrhaphy of collaterals. Intra-operative finding of T1aE in the context of aneurismal rupture and hemodynamic instability, forced us into an inventive solution aiming to regain proximal sealing. This was essentially a variant of previously described proximal banding for T1aE. Endoprosthesis explantation was considered too time-consuming and aggressive in an already unstable patient. Results at 2-year follow-up were encouraging.